In vitro efficacy of Rosmarinus officinalis L. leaves ethanolic extract and essential oil against head lice - قاسم, عبير; سوزان سمرة; كنعان التميمي; منال درويش (Latakia University Journal -Medical Sciences Series, 2024)
Introduction: Head lice infestation is one of the most important public health proplems among children worldwide, its treatment is challenging because of the toxicity and the increased resistance to the existing treatments. Therefore, it’s important to find alternative non-toxic anti-lice agents to overcome this problem. Objective: This study aims to test the efficacy of essential oil and ethanolic extract from Rosmarinus officinalis L. leaves and compare their activity with benzyl benzoate in vitro. Materials and methods: The leaves of Rosmarinus officinalis L. were collected from Banias City, Syria. Essential oil was extracted from dried and powdered leaves by hydrodistillation using a modified Clevenger apparatus. Ethanolic extract was prepared from leaves powder using Soxhelt. A filter paper diffusion bioassay was carried out to determine the pediculicidal activity of ethanolic extract and essential oil from Rosmarinus officinalis L. leaves and comparing their activity with benzyl benzoate lotion, 4µl/cm2 was an appropriate starting dose for screening. Results: In a filter paper contact bioassay with P. humanus capitis females at 4 µl/cm 2 , the results showed that Rosemary essential oil ethanolic solution 800 µl/ml with LT50= 0.17h was more toxic than Rosemary ethanolic extract 25 mg/ml with LT50= 1.99h, but both were less effective than benzyl benzoate lotion with LT50= 0.03h. Conclusion: The results demonstrate Rosemary essential oil in our study was more toxic than Rosemary essential oil in other studies and Rosemary ethanolic extract has good mortality against head lice, both of them can use in preparation the pediculicdal commercial product .